Application of Topsis Method in Selection of Fire Fighter Squad Commanders at Percut Sei Tuan Post - Nuraisana Nuraisana (INFOKUM, 2021)
Fire is an uncontrollable event as a result of a rapid exothermic oxidation reaction that is accompanied by the emergence of fire/ignition that can cause loss of property, soul and ecology. The Fire Station Percut Sei Tuan is Located at Jln. West Irian, Sempali Village Percut Sei Tuan is one of the Fire Station in Deli Serdang. A squad commander is in charge of being in charge and giving instructions to members. The problem that is often faced in the selection of a squad commander is the difficulty of conducting a performance assesment in determining who is worthy to be the right squad commander. The purpose of this study was to determine which firefighters were entitled and worthy to be the commander of the squad at the percut sei Tuan post based on existing criteria without differentiating their existing social status. For that we need a decision support system that is able to assist in decision making where the decision is not yet known what decision will be taken. By using the TOPSIS method, it is possible to determine the squad commander at the Percut Sei Tuan post quickly and accurately.